2013
DOI: 10.1111/apha.12172
|View full text |Cite
|
Sign up to set email alerts
|

Physiology and analysis of the electrocardiographic T wave in mice

Abstract: The end of the T wave is readily available from conscious and anaesthetized mice. Heart rate correction of QT interval duration in the anaesthetized mouse is not recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(83 citation statements)
references
References 23 publications
2
80
1
Order By: Relevance
“…Previous studies have demonstrated that this dose or less causes a significant tachycardia in normal mice (21, 24-26). Serial ECGs were recorded from CLP mice at 25 h post-surgery before and after administration of isoproterenol.…”
Section: Resultsmentioning
confidence: 86%
“…Previous studies have demonstrated that this dose or less causes a significant tachycardia in normal mice (21, 24-26). Serial ECGs were recorded from CLP mice at 25 h post-surgery before and after administration of isoproterenol.…”
Section: Resultsmentioning
confidence: 86%
“…5B)in a manner similar to those described previously in mice[ 40]. In an attempt to quantify the magnitude of ECG alternans, we estimated the T-wave alternans ratio using the method described previously [40,41]. We found that the T -wave alternans ratio was significantly higher in RyR2 -SOF mice than that in RyR2-WT mice (Fig.…”
Section: Resultsmentioning
confidence: 69%
“…To test this possibility, we performed telemetric ECG recordings on conscious RyR2-WT and RyR2-SOF mutant mice at rest and after the injection of isoproterenol (ISO), which was used to induce alternans[ 40,41]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that inhaled isoflurane anesthesia reduces heart rate, and therefore increases QT-intervals. However, amplitude of recovery T-waves remains unaffected 18 .…”
Section: Representative Resultsmentioning
confidence: 99%